The Description of the Depression Level at the Orphanage of Elderly - Susanti, Yulia; Nasihah, Azidatun; PH, Livana; Nurwijayanti, Andriyani Mustika (GLOBAL HEALTH SCIENCE GROUP, 2022)
The elderly will do the aging process and change the physical and psychologically, this change can affect the health problems such as depression. Depression is often undetected among the elderly because of the aging process and chronic disease among elderly. Use quantitative methods with the descriptive design study. The number of samples is 64 elderly. Sampling techniques use purposive sampling. The research was done at the Orphanage for the Elderly at the Kendal District. The instrument used is the questionnaire of the Geriatric Depression Scale (GDS). The result showed that the majority of the elderly aged was 60 – 73 years, female, and not in school attendance. The level of depression among the elderly is moderate category is 37 elderly (57,8%). The orphanage nurse can deliver activity on the development of group activity therapy, facilitate the elderly to communicate with family when they want to meet with the family to reduce the depression level since they stay at the boarding house.